(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the clinical and paraclinical characteristics of fetal anemia cases treated with intrauterine transfusion at Hanoi Obstetrics and Gynecology Hospital. Materials and Methods: A prospective case series study was conducted on 05 fetuses diagnosed with anemia (MCA-PSV > 1.5 MoM and/or hydrops fetalis) at the Fetal Intervention Center, Hanoi Obstetrics and Gynecology Hospital, from April 2023 to April 2025, treated with intrauterine blood transfusion. Results: The mean maternal age was 32.2 ± 2.77 years. The mean gestational age at diagnosis was 28.21 ± 3.02 weeks. The primary etiologies of anemia included complications of monochromatic twin pregnancies (4/5 cases), Parvovirus B19 infection (1/5 cases), and immune-mediated alloimmunization due to atypical antibodies (1/5 cases). Ultrasound findings revealed hydrops fetalis in 60%, cardiomegaly in 80%, and abnormal umbilical cord insertion (velamentous/marginal) in 60%. Conclusion: Intrauterine transfusion (IUT) is an effective intervention for managing severe fetal anemia. However, late diagnosis remains a significant challenge, emphasizing the need for enhanced screening using MCA-PSV Doppler during the second trimester, particularly in high-risk pregnancies.